2009
DOI: 10.1080/14992020802607431
|View full text |Cite
|
Sign up to set email alerts
|

Normal-hearing English-as-a-second-language listeners’ recognition of English words in competing signals

Abstract: English-as-a-second-language (ESL) listeners have difficulty perceiving English speech presented in background noise. The current study furthered this line of investigations by including participants who varied widely in their age of English acquisition and length of English learning: 24 native English monolingual (EML), 12 simultaneous bilingual (SBL), 10 early ESL (E-ESL), and 14 late ESL (L-ESL) listeners. Word recognition scores were obtained in quiet and in the presence of speech-weighted noise, multi-tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 49 publications
6
39
3
1
Order By: Relevance
“…Different from previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012;Jin and Liu, 2014), we found a significant difference between CN L1 and L2 perception with only with interfering babble, not with SSN. Consistent with previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012), the difference in performance between L1 and L2 was greater for babble than for SSN. Interestingly, a slight release from masking (babble DRT -SSN DRT) was only observed for L1 in CN subjects; L1 performance with babble slightly worsened for EN subjects, relative to SSN.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Different from previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012;Jin and Liu, 2014), we found a significant difference between CN L1 and L2 perception with only with interfering babble, not with SSN. Consistent with previous studies (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012), the difference in performance between L1 and L2 was greater for babble than for SSN. Interestingly, a slight release from masking (babble DRT -SSN DRT) was only observed for L1 in CN subjects; L1 performance with babble slightly worsened for EN subjects, relative to SSN.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, non-native listeners in the "real" world must overcome both "imperfect" signals and knowledge of L2. Under adverse listening conditions, L2 listeners are more susceptible to interfering noise than are L1 listeners, regardless of speech stimulus type (phoneme, word, or sentence) (Rogers et al, 2006;Cooke et al, 2008;Shi, 2009;Broersma and Scharenborg, 2010;Garcia Lecumberri et al, 2010;Jin and Liu, 2012). Noise can interfere with speech by overlapping the target speech spectrum ("energetic masking") and/or by presenting temporal information that is similar to the target temporal envelope ("informational masking").…”
Section: Introductionmentioning
confidence: 99%
“…Many bilingual listeners learned the second language later in life; as a consequence, it is difficult for them to master the language to the same degree as a native listener. Numerous studies exist to substantiate this point of view (e.g., Flege, MacKay, & Meador, 1999;Mayo, Florentine, & Buus, 1997;Nakamura & Gordon-Salant, 2011;Rogers, Lister, Febo, Besing, & Abrams, 2006;Shi, 2009Shi, , 2010Stuart, Zhang, & Swink, 2010;von Hapsburg & Bahng, 2006;von Hapsburg, Champlin, & Shetty, 2004;Weiss & Dempsey, 2008). Stuart et al (2010), for instance, presented English sentences in noise to late MandarinEnglish bilinguals (age of acquisition: 10-13 years).…”
mentioning
confidence: 96%
“…As shown earlier, many bilingual studies demonstrated that bilingual individuals' word recognition is affected by their language background to a higher degree in noise than that in quiet (e.g., Rogers et al, 2006;Shi, 2009;Shi & Sánchez, 2010). In one study (Shi & Sánchez, 2010), Spanish-English bilinguals' recognition of English and Spanish words was analyzed at different SNRs.…”
mentioning
confidence: 98%
“…In both datasets, the variance in estimates of SRT for the non-native and native listeners was comparable (0.9 dB in the present study). Some studies have reported greater individual differences in non-native than native speakers (e.g., Mayo et al, 1997), a result that likely reflects heterogeneity in the general population of non-native speakers with different linguistic backgrounds (Shi, 2009). These observations highlight the fact that the present results may not extend to listeners who acquired English prior to 10 yrs of age.…”
Section: Non-native Late Learnersmentioning
confidence: 99%